The Effect of Multimedia-Based CIRC Learning Model on Thematic Learning Outcomes - Khairani, Fadhilah; Ambarita, Alben; Diana, Siska Mega; Elsiyana, Efti (Jurnal Pendidikan Progresif, 2022)
The Effectiveness of Multimedia-Based Cooperative Integrated Reading and Composition (CIRC) on Thematic Learning Outcomes. Objectives: The low students’ learning outcomes encourage this study to analyze and determine the effect of the implementation of the multimedia-based Cooperative Integrated Reading and Composition (CIRC) learning model on the students’ thematic learning outcomes. Methods: Quasi-experimental and quantitative approaches were employed in this study with a non-equivalent control group design. The purposive sampling technique was used in determining the research sample from a total population of 59 students. The data were collected through test and non-test techniques. Findings: Based on the hypothesis test using a simple regression formula, the data obtained that Fcount > Ftable, i.e., 9.19 > 4.20, which has a positive and significant effect on students’ learning outcomes after the implementation of the CIRC model combined with multimedia. Conclusion: The CIRC learning model applied is concluded as an effective learning model as it could improve students’ learning outcomes. Keywords: CIRC, multimedia, thematic learning outcome.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202204